Potential benefits of using chitosan and silk fibroin topical hydrogel for managing wound healing and coagulation - Soumya Narayana; Arfa Nasrine; Mohammed Gulzar Ahmed; Rokeya Sultana; B.H. Jaswanth Gowda; Suprith Surya; Mansour Almuqbil; Syed Mohammed Basheeruddin Asdaq; Sultan Alshehri; Syed Arif Hussain (Elsevier, 2023)
Background & Objectives: The intricate process of wound healing involves replacing the cellular or tissue structure that has been destroyed. In recent years various wound dressings were launched but reported several limitations. The topical gel preparations are intended for certain skin wound conditions for local action. Chitosan-based hemostatic materials are the most effective in halting acute hemorrhage, and naturally occurring silk fibroin is widely utilized for tissue regeneration. So, this study was conducted to evaluate the potential of chitosan hydrogel(CHI-HYD) and chitosan silk fibroin hydrogel (CHI-SF-HYD) on blood clotting and wound healing. Methods: Hydrogel was prepared using various concentrations of silk fibroin with guar gum as a gelling agent. The optimized formulations were evaluated for visual appearance, Fourier transforms infrared spectroscopy (FT-IR), pH, spreadability, viscosity, antimicrobial activity, HR-TEM analysis, ex vivo skin permeation, skin irritation, stability studies, and in vivo studies by using adult male Wistar albino rats. Results: Based on the outcome of FT-IR, no chemical interaction between the components was noticed. The developed hydrogels exhibited a viscosity of 79.2 ± 4.2 Pa.s (CHI-HYD), 79.8 ± 3.8 Pa.s (CHI-SF-HYD), and pH of 5.87 ± 0.2 (CHI-HYD), 5.96 ± 0.1 (CHI-SF-HYD). The prepared hydrogels were sterile and non-irritant to the skin. The in vivo study outcomes show that the CHI-SF-HYD treated group has significantly shortened the span of tissue reformation than other groups. This demonstrated that the CHI-SF-HYD could consequently accelerate the regeneration of the damaged area. Interpretation & Conclusion: Overall, the positive outcomes revealed improved blood coagulation and re-epithelialization. This indicates that the CHI-SF-HYD could be used to develop novel wound-healing devices.